Entrepreneurial Accounting as a Driver of SMEs’ Sustainability: A Systematic Review - Isiaka Mustapha; Olalekan Busra Sakariyau; Umaru Mustapha Zubairu; Moruf Jimoh (Journal of Business and Behavioural Entrepreneurship, 2023)
Purpose: This paper conducted a systematic review of entrepreneurial accounting (EA) articles published over the last ten years (2012 – 2022). Using the Systematic Qualitative Assessment Techniques (SQAT) to review 79 EA journal articles to provide an understanding of the antecedent and importance of the concept on business venture survival or otherwise. Methodology: This paper analysed the time distribution, geographic distribution, theory used, article type, data collection methodologies and themes of the EA article reviewed. Findings: The key findings show that EA interest has increased in Asia and Africa over the last decade, while Oceania (Australasia) were least represented. The most striking theme out of the five identified is the impact of EA as the heart of business ventures’ sustainability, while the resource-based theory was most used to provide a clear understanding of the concept of the need for inherent management and cost accounting skills. Implications: Findings from the review confirm the importance of entrepreneurial accounting (EA) in SMEs as scholarly work has increased in recent times in the most developing economies, especially in Asia and Africa. This study recommended that EA skills should form part of the funding requirements for start-ups in accessing finance. Keywords: entrepreneurial accounting, systematic review, sustainability, financial literacy.